Epidemiological profile of dog attacks to patients under 14 years old assisted at the pediatric referral emergency unit of a tertiary hospital in Campinas, Brazil - Medeiros, Michelle Marchi; Marson, Fernando Augusto Lima; Marques, Leonardo Souza; Peixoto, Andressa Oliveira; Fraga, Andrea de Melo Alexandre (Frontiers in Pediatrics, 2022)
Introduction: Accidents involving dog attacks are very common, which makes this type of accident a global public health issue. The estimates point to 20% of the victims of such accidents seeking care in health units, and half of them being children. In addition to acute injuries, dog attacks might result in fractures, infections, scars, and psychological traumas. This study aimed to describe the epidemiological profile of dog attacks to children under 14 years old assisted in a pediatric emergency service in Brazil. Methods: The database of the Information and Toxicological Assistance Center of Campinas was surveyed to identify cases of children under 14 years old assisted after a dog attack in a 9-years period. Demographic data, number and type of lesions, type of exposure, part of the body affected, dog origin and condition, and the accident location and cause were analyzed. The data were presented in a descriptive way, and the age groups were classified as follows: 0-3 years old, 4-6 years old, and 7-14 years old. The different age groups were compared one to another regarding the markers evaluated using the chi-square test and the Fisher’s exact test. A 0.05 alpha was adopted in all analyses. Results: The number of children assisted in the study period totaled 1,012. The 7-14-year-old group was the most affected (n=498; 49.2%), male patients were also majority (n=660; 65.2%). Most injuries were found on the head/neck area (n=378; 37.4%). However, the older the patients were, the higher the frequency of lesions on upper and lower limbs was, as well as attacks occurred in external environments, thus involving animals that could not be observed. A significant increase in accidents with provoked causes was observed in younger patients. Conclusion: Accidents involving dog attacks are more likely to happen among boys. Younger children run higher risks of becoming victims of these accidents inside homes, being attacked by pets, and showing a greater incidence of head and neck lesions. Older children present more injuries on their limbs, which are caused by dogs that cannot be observed.